2010
DOI: 10.1002/asia.201000372
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Synthesis of a Combinatorial Methylated (±)‐Epigallocatechin Gallate Library and the Growth‐Inhibitory Effects of these Compounds on Melanoma B16 Cells

Abstract: We report on the solid-phase synthesis of a combinatorial methylated (±)-epigallocatechin gallate (EGCG) library and its biological evaluation. Epigallocatechin gallate (EGCG) and its methylated derivatives, which are members of the catechin family, exhibit various anti-cancer effects. The solid-phase synthesis of methylated EGCG involves the preparation of the α-acyloxyketone by the coupling of a solid-supported aldehyde with a ketone and an acid. The subsequent release and reductive etherification reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For example, one of the methylation products, 7-OMe EGCG, was shown to have equal efficacy but increased bioavailability when compared to EGCG [26]. Given the aggressive nature of melanomas, effective therapies may most likely involve a combinational approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the methylation products, 7-OMe EGCG, was shown to have equal efficacy but increased bioavailability when compared to EGCG [26]. Given the aggressive nature of melanomas, effective therapies may most likely involve a combinational approach.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the PDE5 inhibitor vardenafil sensitized MM cells to a methylated EGCG derivative that has been known to enhance pharmacokinetic characteristics compared with EGCG in plasma (43). Various types of EGCG derivatives can be produced by solidphase synthesis (44). Appropriate EGCG derivatives may improve the pharmacokinetic characteristics as activators of 67LR.…”
Section: Pde5 Is Overexpressed In Various Types Of Human Cancer and mentioning
confidence: 99%
“…Takahashi and co-workers described the efficient solid-phase synthesis of EGCG (see Figure 1) and the combinatorial synthesis of protected methylated epicatechin derivatives 35 (2,3-disubstituted benzopyran derivatives) (Scheme 7) [61,62].…”
Section: Solid-phase Synthesis Of Substituted Benzopyran Compoundsmentioning
confidence: 99%